Idiopathic Spinal Epidural Lipomatosis: Unusual Presentation and Difficult Management - Ouidad Louachama; Noureddine Rada; Ghizlane Draiss; Mohamed Bouskraoui (Case Reports in Pediatrics)
Epidural lipomatosis (EL) is a pathology characterized by abnormal accumulation of unencapsulated fat in the epidural space. Although rare, it is a possible cause of lumbosciatica or narrow lumbar canal in adults. It is often associated with favorable factors such as prolonged corticosteroid therapy or obesity. We report an observation of an 18-month-old child who presented with walking delay without other abnormalities, and the radiological exploration confirmed the lumbar epidural lipomatosis. The management was mainly symptomatic, based on motor physiotherapy with additional management in neurosurgery. Various etiologies can cause this disease, remain rare in pediatrics, and the idiopathic form is predominant in children.